Dukungan Keluarga dalam Meningkatkan Kualitas Hidup Pasien Kanker Serviks - Rina Delfina; Meriza Putri (DIAGNOSA: Jurnal Ilmu Kesehatan dan Keperawatan, 2024)
Abstract. Cervical cancer is a disease caused by malignant tumors in the uterine area (cervical) as a result of uncontrolled growth of tissue and damage to the surrounding normal tissue. Family as a source of support plays an important role in providing support to improve the quality of life of cancer patients. The purpose of this study was to analyze the relationship between family support and the quality of life of cervical cancer patients. This type of research is descriptive quantitative. The sampling method is by accidental sampling. The sample of this study were cancer patients undergoing treatment with a total of 32 samples. The instrument used is a questionnaire. The results showed that more than half (56.25%) of the respondents were aged 46-65 years, more than half (53%) of the respondents did not work, and some (50%) of the respondents were in stage 3, and most (91%) family support in improving the quality of life of cervical cancer patients. The results of this study can be used as health promotion educational material about risk factors for cervical cancer and to re-effectively provide health counseling services for sufferers and their families who are diagnosed by doctors as having difficult cases to recover, so that patients can express their feelings about the illness they are suffering from so that it has an impact on their quality of life. better. Abstrak. Kanker serviks merupakan penyakit akibat tumor ganas pada daerah rahim (leher rahim) sebagai akibat dari adanya pertumbuhan jaringan yang tidak terkontrol dan merusak jaringan normal disekitarnya. Keluarga sebagai sumber dukungan berperan penting dalam memberikan dukungan untuk meningkatkan kualitas hidup pasien kanker. Tujuan penelitian untuk menganalisis hubungan antara dukungan keluarga dengan kualitas hidup pasien kanker servik. Jenis penelitian ini adalah deksripti kuantitatif. Cara pengambilan sampel dengan cara accidental sampling. Sampel penelitian ini adalah pasien kanker yang menjalani pengobatan dengan jumlah 32 sampel. Instrument yang digunakan adalah kuesioner. Hasil penelitian menunjukan bahwa lebih dari sebagian (56,25%) responden berusia 46-65 tahun, lebih dari sebagian (53%) responden tidak bekerja, dan sebagian (50%) responden berada pada stadium 3, dan sebagian besar (91%) keluarga mendukung dalam meningkatkan kualitas hidup pasien kanker serviks. Hasil penelitian ini dapat digunakan sebagai bahan edukasi promosi kesehatan tentang faktor risiko kanker serviks dan mengefektifkan kembali layanan konsling kesehatan untuk penderita dan keluarga yang didiagnosa oleh dokter mengidap kasus sulit untuk sembuh, sehinga pasien dapat mengkungkapkan perasaan mengenai penyakit yang dideritanya sehingga berdampak pada kualitas hidup yang lebih baik.